A Prospective Study of Burn Deaths with Special Reference to Manner of Death and Duration of Survival (Indian Journal of Forensic Medicine & Toxicology, 2021)
Around 0.2 million people are admitted in hospital due to burns, of which about 5000 people die every year.4Extent of Total Body Surface Area involved is an important parameter, that affects the prognosis in case ofburn injury. The majority of fire related deaths are accidental, usually due to carelessness. Suicidal burns aremostly seen in domestic situations and in females. Homicidal burns are rare; mostly accomplished to takerevenge or to conceal crime. So, this study was carried out with the aim to estimate the total body surfacearea affected & duration of survival / hospital stay and to find out the manner of death in burn cases.It was found that 79.00% cases had burn injuries covering 60– 100% of the total body surface area (TBSA).Maximum percentage of burns was seen in females (30.00% cases) with TBSA of 80-90%. 95% cases werehospitalized with 75.00% having the hospitalization period of 1 – 10 days and maximum number of cases(33%) survived for a period of 3 to 5 days. In most of the cases (64.00%), the manner of death was accidentalfollowed by suicidal (34.00%), with only 2% cases of homicidal burns.
Keywords: burn deaths, manner of death, total body surface area, duration of survivl.